Ekologi : Pandangan Iman KristententangPermasalah Alam - Yohanis Rantelangan (Pustaka Peradaban, 2023)
The current conservation efforts face serious challenges. Conservation is not universally regarded as a moral endeavor that should be embraced by everyone. It is perceived as if environmental concerns and conservation initiatives solely fall under the responsibility of conservation communities. However, environmental issues and nature preservation are complex matters that necessitate collaboration and involvement from various parties, including individuals, governments, and interfaith communities. Hence, there is a need to foster collective awareness and integrate moral values into conservation endeavors to attract participation from a diverse range of stakeholders. This is where the actualization of Christian conservation values becomes crucial. Essentially, nature preservation is an inherent value within the Christian tradition. From a Christian perspective, humanity is considered stewards and custodians of God's creation. Individuals are entrusted with the responsibility to care for and safeguard the natural environment as an expression of reverence towards the Creator and an active embodiment of faith. Christians are also taught to extend love and compassion to fellow creatures of God, including nature and other living beings. This love encompasses attitudes of attentiveness, respect, and protection towards all of God's creations. Upaya konservasi dunia saat ini menghadapi tantangan dan masalah serius. Konservasi dianggap bukan sebagai upaya moral yang harus dilakukan oleh semua orang. Seolah-oleh masalah lingkungan dan upaya konservasi hanyalah tanggung jawab komunitas konservasi saja. Padahal masalah lingkungan dan pelestarian alam adalah isu kompleks yang memerlukan kerjasama dan keterlibatan dari berbagai pihak, termasuk individu, pemerintah, dan komunitas lintas Iman. Karena itu perlu upaya untuk memunculkan kesadaran kolektif dan mengintegrasikan nilai-nilai moral dalam upaya konservasi untuk menarik keterlibatan lebah banyhak pihak. Disinilah perlu adanya aktualisasi kembali nilai konservasi Kristen. Karena pada dasarnya nilai pelestarian alam adalah nilai yang inhern dalam tradisi Kristen. Dalam pandangan Kristen, manusia dianggap sebagai kustodian atau pemelihara ciptaan Tuhan. Manusia diberi tanggung jawab untuk merawat dan menjaga lingkungan alam sebagai bentuk penghormatan terhadap pencipta dan sebagai ekspresi dari iman yang aktif. Manusia juga diajarkan untuk mencintai sesama makhluk Tuhan, termasuk alam dan makhluk hidup lainnya. Cinta kasih ini mencakup sikap perhatian, menghormati, dan perlindungan terhadap semua ciptaan Tuhan.